Analisis Faktor Kecelakaan dan Keselamatan Kerja Pada Penggunaan Hoist Crane Menggunakan Metode Varimax - Akhmad I. Fajar; Rusindiyanto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Occupational safety and health (OSH) is a critical issue that affects operational performance and sustainability in industry. The use of overhead travelling cranes, while supporting process efficiency, carries a significant risk of occupational accidents. The aim of this study is to analyse the factors influencing occupational accidents and OSH in hoist crane operations using the varimax rotation method. The research data was collected through questionnaires distributed to workers in companies using hoisting cranes. The analysis covered three main aspects: human factors, environmental factors and equipment factors. The results showed that human factors include physical condition, discipline, operator skill and carelessness. Environmental factors included plant layout, communication, cleanliness and site conditions. As for equipment factors, the condition, maintenance, feasibility and completeness of equipment are important aspects that affect work safety. The research found that work accidents can be minimised by focusing on the dominant factors identified. With these findings, the research provides strategic recommendations for companies to systematically manage occupational risks, improve occupational safety and reduce the potential for accidents, particularly in the use of heavy equipment such as hoisting cranes.